2023
DOI: 10.1093/jee/toad003
|View full text |Cite
|
Sign up to set email alerts
|

Distance-based Decision-making in Oviposition byTribolium castaneumHerbst (Coleoptera: Tenebrionidae) on Low- and No-gluten Flours

Abstract: The increasing popularity of low- and no-gluten flours as wheat flour alternatives has driven the need to understand risks of insect pest infestation in these products. Previous research using no-choice bioassays found that the red flour beetle, Tribolium castaneum Herbst can oviposit and develop on a range of alternative flours; here we test T. castaneum preference by assessing attraction in a wind tunnel assay and oviposition preference in both small- and large-scale choice assays between alternative and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…One of the key cues used by stored product insects in foraging are food cues from post-harvest commodities (reviewed in 45). For example, prior work has found that host cues from grain are broadly attractive to a range of stored product insects, including T. castaneum and R. dominica 45 50 . Out of seven plant species, R. dominica was most attracted to wheat, which was found to be most suitable for its development 51 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the key cues used by stored product insects in foraging are food cues from post-harvest commodities (reviewed in 45). For example, prior work has found that host cues from grain are broadly attractive to a range of stored product insects, including T. castaneum and R. dominica 45 50 . Out of seven plant species, R. dominica was most attracted to wheat, which was found to be most suitable for its development 51 .…”
Section: Introductionmentioning
confidence: 99%